3D printing of strontium-doped hydroxyapatite based composite scaffolds for repairing critical-sized rabbit calvarial defects. (24th August 2018) - Luo, Yun; Chen, Shangsi; Shi, Yufei; Ma, Jun
Abstract: In this study, strontium substituted hydroxyapatite (Sr-HAP) was synthesized using collagen type I and citrate as bi-templates and the obtained nanoparticles with high similarity to natural bone minerals were made into composite scaffolds with interconnected porous structure using a three-dimensional (3D) printing technique. A calcium deficient structure of HAP phase was caused by doping Sr which was verified by Fourier transform infrared, x-ray diffractometer, scanning electron microscopy and transmission electron microscopy. The Sr/(Sr + Ca) molar ratio in Sr-HAP nanoparticles was 5.8% estimated by EDX. Furthermore, both 3D printed scaffolds made of Sr-HAP and HAP had uniform porous structure and porosity of about 60%. Cell culturing indicated that MC3T3-E1 cells could adhere on the surface of the scaffolds and the strontium substitution could enhance cell adhesion, proliferation and alkaline phosphatase activity. The printed composite scaffolds were used to repair critical-sized rabbit calvarial defects with a diameter of 15 mm. The results showed that the Sr-HAP scaffolds had better osteogenic capability and stimulated more new bone formation within 12 weeks. It was suggested that these printed Sr-HAP composite scaffolds possessed high potential as candidates in the application of bone augmentation and regeneration.